PERAN PARENTING DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI LEMBAGA PAUD SURAKARTA - M. Hery Yuli Setiawan; Feri Faila Sufa (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
The purpose of this study was to (1) describe the forms of learning, (2) Implementation of learning the characters and (3) determine whether the story-telling method can improve the character of the Early Childhood through Storytelling Method in improving discipline. The method that used in this study is action research class. The conclusions of this study were (1) The values of character education in particular discipline can be implanted (build up) in early childhood through Spiritual Aspect, Personal Aspect / personality, Social Aspect, and environmental aspects. (2) In implementation needed a model and examples of discipline from educators and parents that’sdemonstrated in early childhood to build character education (3) The method of storytelling is capable of carrying a classroom atmosphere to be more natural, and it also capable of being the media to move the rule of discipline character values of discipline in a child so grow and increase. Children are more receptive to the moral values of discipline from a story. Thus, the story method have an important role in the socialization of  a new values to the children.